2020
DOI: 10.1038/s41598-020-61247-0
|View full text |Cite|
|
Sign up to set email alerts
|

Artificial Intelligence based Models for Screening of Hematologic Malignancies using Cell Population Data

Abstract: Cell Population Data (CPD) provides various blood cell parameters that can be used for differential diagnosis. Data analytics using Machine Learning (ML) have been playing a pivotal role in revolutionizing medical diagnostics. This research presents a novel approach of using ML algorithms for screening hematologic malignancies using CPD. The data collection was done at Konkuk University Medical Center, Seoul. A total of (882 cases: 457 hematologic malignancy and 425 hematologic nonmalignancy) were used for ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 28 publications
0
14
2
2
Order By: Relevance
“…In another study by Virk et al, the clinical utility of the CPD parameters, scatter grams, and flags by generating statistical equations for screening of AML cases was published [ 34 ]. Here, an exception is found in studies conducted by Shabbir et al [ 35 ] and our work (Haider et al) [ 36 ], wherein ML tools were challenged for discernment between just two study groups (hematologic vs. non-hematologic malignancies and acute promyelocytic leukemia vs. other hematologic malignancies, respectively).…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…In another study by Virk et al, the clinical utility of the CPD parameters, scatter grams, and flags by generating statistical equations for screening of AML cases was published [ 34 ]. Here, an exception is found in studies conducted by Shabbir et al [ 35 ] and our work (Haider et al) [ 36 ], wherein ML tools were challenged for discernment between just two study groups (hematologic vs. non-hematologic malignancies and acute promyelocytic leukemia vs. other hematologic malignancies, respectively).…”
Section: Discussioncontrasting
confidence: 59%
“…Here, an exception is found in studies conducted by Shabbir et al [35] and our work (Haider et al) [36], wherein ML tools were challenged for discernment between just two study groups (hematologic vs. non-hematologic malignancies and acute promyelocytic leukemia vs. other hematologic malignancies, respectively).…”
Section: Discussioncontrasting
confidence: 57%
“…Generally, routine blood exams data in numerical form such as Whole Blood Cells count, blood sugar level, Hemoglobin, etc., can be used as a feature set to build classification and regression models. Combining blood tests with advanced AI-based methods can significantly improve the sensitivity and accuracy of diagnosis [ 105 , 106 , 107 ]. In the recent past, several studies have been published which show the applicability of these techniques in predicting common diseases [ 107 , 108 ].…”
Section: Role Of Ai In the Screening Of Covid-19 Infected Patients And Diagnosismentioning
confidence: 99%
“…Artificial intelligence has recently attracted much attention in various fields of health and medicine. Different artificial intelligence and machine learning (ML) methods have been applied for various purposes, including image recognition, patient phenotyping, and outcome prediction for diseases such as cancer [15][16][17][18][19], cardiac arrest [20], Alzheimer's disease [21][22][23], respiratory diseases [24,25], rheumatic diseases [26], cornea and retinal diseases [27,28], gastrointestinal diseases [29,30], and infectious diseases [31][32][33][34][35]. These studies revealed that artificial intelligence has the capacity to assist clinicians in the disease diagnosis with high efficiency and accuracy.…”
Section: Introductionmentioning
confidence: 99%